G-Quadruplexes as tools for synthetic biology - Agarwala, Prachi; Pandey, Satyaprakash; Maiti, Souvik (Chembiochem, 2013)
With the potential to engineer biological systems, synthetic biology is an emerging field that combines various disciplines of sciences. It encompasses combinations of DNA, RNA and protein modules for constructing desired systems and the rewiring of existing signalling networks. Despite recent advances, this field still lags behind in the artificial reconstruction of cellular processes, and thus demands new modules and switches to create genetic circuits. The widely characterised noncanonical nucleic acid secondary structures, G-quadruplexes are promising candidates to be used as biological modules in synthetic biology. Structural plasticity and functional versatility are significant G-quadruplex traits for its integration into a biological system and for diverse applications in synthetic circuits.
Keywords: G-quadruplexes; ribozymes; synthetic biology; topology; zipcodes

Critical role of select peptides in the loop region of G-rich PNA in the preferred G-quadruplex topology and stability - Bose, Tanaya; Kumar, Vaijayanti A. (Tetrahedron, 2017)
An uncharged PNA 15mer sequence formed unimolecular antiparallel G-quadruplex similar to that observed for DNA-TBA. Replacement of `tt' loop regions by peptides which induce helices or turns were found to have unpresidented effect on the quadruplex topology and stability. This study opens up a completely new strategy of utilizing G-quadruplex formation to display the array of functional groups in the three dimensional space thus creating a possibility of getting closer to the dream of designed peptides with three dimensional structures as observed in catalytic protein folds. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: ESI-MS study; G-quadruplex; Peptide nucleic acid; topology

Engineering molecular topology: A pseudopeptidic macrocyclic figure-eight motif - Sharma, Sakshi; Thorat, Shridhar H.; Gonnade, Rajesh G.; Jasinski, Jerry P.; Butcher, Ray; Haridas, V. (European Journal of Organic Chemistry, 2017)
We herein present a rational-design strategy for the synthesis of molecules with figure-eight topology. The design concept is based on the incorporation of turn units in the back-bone of the macrocycle. The molecular structures and the folding are studied by X-ray crystallography and NMR, FT-IR, and CD spectroscopy.
Keywords: Macrocycles; noncovalent interactions; Pi interactions; topology; X-ray diffraction